Alternated Q-switched and gain-switched dual-pulse Yb fiber laser with Tm-Ho co-doped fiber as saturable absorber. (May 2019) - Yang, Song; Yang, Ying-Ying; Zhang, Ling; Huang, Jun-Yuan; Bai, Yun-Rui; Wang, Yu; Lin, Xue-Chun
Highlights: We demonstrate a dual-wavelength and dual-pulse Yb-doped fiber with a Tm-Ho co-doped fiber as saturable absorber. The pulse at 1064 nm is generated via SA-induced self Q-switching. The pulse at 2127.7 nm is generated by gain-switching with the laser at 1064 nm as the pump for the Tm-Ho co-doped fiber. The pulse duration of the laser at 1064 nm can reach up to 1.4 μs. Abstract: We demonstrate a dual-wavelength and dual-pulse Yb-doped fiber laser with a Tm-Ho co-doped fiber as saturable absorber (SA). The wavelength of the first pulse in the dual-pulsing output is at 1064 nm generated via SA-induced self Q-switching and the second pulse is at 2127.7 nm and generated by gain-switching with the laser at 1064 nm as the pump for the Tm ions in the Tm-Ho co-doped fiber and thus induced stimulated emission. With the increases of the pump power, the pulse duration of the two pulses is decreased depending on the level of the pump. The pulse duration of the laser at 1064 nm decreases from 1.4 μs to 296 ns when the pump power increases from 275 mW to 475 mW, while the pulse duration at 2127.7 nm is reduced from 440 ns to 246 ns when the pump increases from 300 mW to 475 mW. Accordingly, the repetition rate is decreased from 17.4 kHz to 6.8 kHz. The experimental result shows that Tm-Ho co-doped fiber is an excellent candidate for SA-induced Q-switching at 1064 nm.